2021
DOI: 10.4081/oncol.2021.518
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive treatment of myxopapillary ependymoma running head: Myxopapillary ependymoma

Abstract: Myxopapillary ependymoma are rare tumors and optimal therapeutic strategy is remained controversial. The main treatments for myxopapillary ependymoma tumors include surgery and radiotherapy. Hence, the present study aimed to review adjuvant treatment of myxopapillary ependymoma, focusing on spinal myxopapillary ependymoma. The information sources of all articles were the English authoritative databases including PubMed, Web of science, Scopus, Science direct and Google scholar. In this review study, the keywor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Comparing our clinical case with previously published articles, we observe a limited number of published cases of myxopapillary ependymoma [ 13 , 14 ], and even fewer clinical cases with such giant tumors.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Comparing our clinical case with previously published articles, we observe a limited number of published cases of myxopapillary ependymoma [ 13 , 14 ], and even fewer clinical cases with such giant tumors.…”
Section: Discussionsupporting
confidence: 56%
“…The tumor’s location near critical structures, such as nerves and blood vessels, can make surgical removal quite complicated [ 13 , 14 ]. While surgery is often the primary treatment, achieving complete resection without causing neurological deficits is a major challenge for neurosurgeons [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another retrospective review of 58 patients undergoing surgical resection found a trend toward improved disease control with the utilization of adjuvant radiotherapy for disease with capsular invasion [ 15 ]. In a contemporary literature review of adjuvant management strategies for MPE, Jahanbakhshi et al identified mixed data for adjuvant radiotherapy while confirming maximal surgical resection as the most important therapy for improving patient outcomes [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, the consensus optimal treatment strategy is similar to ependymoma at large, wherein maximal safe surgical resection is recommended [ 11 , 12 , 13 ]. The role of chemotherapy and radiotherapy remains controversial [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%